PROBLEMATIKA PELAKSANAAN EKSEKUSI PIDANA MATI OLEH KEJAKSAAN TERHADAP TERPIDANA NARKOTIKA - Fuad Nur; Lade Sirjon (Universitas Negeri Makassar, 2023)
This study aims to find out the role of the prosecutor's office in the application of the death penalty to narcotics crimes and whether there is a problem in the implementation of executions of drug convicts. The type of research used is normative-juridical research accompanied by interview data. The approaches used are the statutory approach and the case approach. Data collection techniques with literature studies accompanied by empirical data in the form of interviews with sources.The technique of data analysis is qualitative through reasoning and legal argumentation. As for the results of the research, the prosecutor's office plays an important role in the application of the death penalty in Indonesia, especially in the case of narcotics crimes. This role is clearly seen when the prosecutor, as the public prosecutor, is able to prove his indictment and charge the defendant with the death penalty, as in the case of Amiruddin or Amir Aco. Based on the indictment and the facts of the trial, the judge also handed down the death penalty, and the verdict has permanent legal force. However, the problem of the execution by the prosecutor's office against the convicted person still exists. The problems are caused by the absence of a decade or time limit for detention for death row inmates, the absence of a period of request for review, the filing of clemency by death row inmates, and the passage of the new Criminal Code, which makes the death penalty an alternatively threatened punishment.Penelitian ini bertujuan untuk mengetahui peran Kejaksaan dalam penerapan pidana mati pada tindak pidana narkotika dan yang menjadi permasalahan dalam pelaksanaan eksekusi mati terhadap terpidana narkotika. Jenis penelitian yang digunakan adalah penelitian yuridis normatif disertai data wawancara. Pendekatan yang digunakan adalah pendekatan perundang-undangan dan pendekatan kasus. Teknik pengumpulan data dengan studi kepustakaan disertai data empiris berupa wawancara. Teknik analisis data adalah kualitatif melalui penalaran dan argumentasi hukum. Adapun hasil penelitian, Kejaksaan berperan penting dalam penerapan pidana mati di Indonesia khususnya pada perkara tindak pidana narkotika. Peran tersebut terlihat jelas ketika Jaksa sebagai Penuntut Umum mampu membuktikan surat dakwaannya dan menuntut terdakwa dengan tuntutan pidana mati sebagaimana perkara Amiruddin alias Amir Aco. Berdasarkan surat dakwaan dan fakta persidangan hakim pun menjatuhkan putusan pidana mati dan putusan tersebut telah berkekuatan hukum tetap. Namun, problematika pelaksanaan eksekusi mati oleh Kejaksaan terhadap terpidana masih saja ada. Permasalahan tersebut disebabkan karena tidak adanya masa daluwarsa atau batas waktu penahanan bagi terpidana mati, tidak adanya jangka waktu permintaan peninjauan kembali, adanya pengajuan grasi dari terpidana mati dan dengan disahkannya KUHP baru menjadikan pidana mati diancamkan secara alternatif.